2015
DOI: 10.1080/15384047.2014.1003005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the hypoxia-activated prodrug TH-302 in combination with gemcitabine and nab-paclitaxel in human tumor xenograft models of pancreatic cancer

Abstract: (2015) Efficacy and safety of the hypoxia-activated prodrug TH-302 in combination with gemcitabine and nab-paclitaxel in human tumor xenograft models of pancreatic cancer, Cancer Biology & Therapy, 16:3,[438][439][440][441][442][443][444][445][446][447][448][449]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 44 publications
(52 reference statements)
2
36
0
Order By: Relevance
“…A similar result was found with a combination of a chemopreventive agent (silibinin) and doxorubicin in which specific drug concentrations of 100 × 10 −6 m silibinin/25 × 10 −9 m doxorubicin produced a synergistic effect in breast cancer cells . Our result is also consistent with a few other studies, including a phase II clinical trial, that demonstrated synergistic effects of TH‐302 combined with chemotherapy and radiotherapy treatments against cancer cells . The enhanced efficacy of doxorubicin at a low concentration of 100 × 10 −9 m by addition of 10 × 10 −6 m TH‐302 is also advantageous from a practical standpoint to prevent/reduce cardiotoxic side effects .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A similar result was found with a combination of a chemopreventive agent (silibinin) and doxorubicin in which specific drug concentrations of 100 × 10 −6 m silibinin/25 × 10 −9 m doxorubicin produced a synergistic effect in breast cancer cells . Our result is also consistent with a few other studies, including a phase II clinical trial, that demonstrated synergistic effects of TH‐302 combined with chemotherapy and radiotherapy treatments against cancer cells . The enhanced efficacy of doxorubicin at a low concentration of 100 × 10 −9 m by addition of 10 × 10 −6 m TH‐302 is also advantageous from a practical standpoint to prevent/reduce cardiotoxic side effects .…”
Section: Resultssupporting
confidence: 90%
“…We used a hypoxia activated prodrug, TH‐302, that has progressed to clinical studies . TH‐302 is reduced under hypoxic conditions, releasing a DNA crosslinker bromo‐isophosphoramide mustard . This mechanism of TH‐302 allows selective drug activation in hypoxic cells in a tumor and has shown hypoxia‐induced cytotoxicity against 32 human cancer cell lines .…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that if tumour-initiating cells (TIC) reside in a hypoxic microenvironment, then they would be sensitive to the hypoxia-activated prodrug TH-302 but relatively resistant to ionizing radiation. TH-302 (evofosfamide) is a 2-nitroimidazole [24-27] whose reductive metabolism produces an alkylating species that causes DNA damage in quiescent as well as proliferating cells. It was recently tested in combination with gemcitabine in a large randomized clinical trial, MAESTRO, treating patients with advanced pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In a xenograft model of pancreatic cancer, TH-302 showed promising activity with gemcitabine, decreasing the frequency of tumor-initiating cells from patient-derived xenografts in combination with ionizing radiation (37). TH-302 also improved the efficacy of a gemcitabine and nab-paclitaxel combination in mouse xenograft models of human pancreatic ductal adenocarcinoma (PDAC) (51). The addition of TH-302 to topotecan improved tumor response and prolonged survival in neuroblastoma and rhabdomyosarcoma xenograft models (52).…”
Section: Clinical–translational Advancesmentioning
confidence: 99%